Thinking About a Past Group Inclusion Experience or a Past Group Exclusion Experience Affects Memory Task Performance. Issue 5 (October 2019) - Wagner, Michael F.; Skowronski, John J.
An experiment examined the impact of thinking about autobiographical group-related events (i.e., a past group inclusion experience or a past group exclusion experience) on recognition memory. After encountering the experimental manipulation, participants studied a list of words. Participants later engaged in two subsequent recognition tests: a group recognition test with a bogus confederate and a surprise individual recognition test. The memory measures were derived from signal detection theory and included hit rates, false alarm rates, and a memory discrimination index. Results showed that exposure to false information produced decreased hit rates, increased false alarms, and lowered discrimination values. Group-related thinking generally impaired recognition memory. These results are discussed in the context of prior research and in the context of theories of false memory.